The problems of adaptation of agrarian enterprises to the conditions of the World trade organization - Arestenko, Tetiana; Арестенко, Тетяна Вікторівна; Арестенко, Татьяна Викторовна; Arestenko, V. (My University, 2008)
Positive and negative influence on competition of agricultural sector of Ukraine in contexts entering to the World Trade Organization are analyzed. The basic problems of increase of competitiveness of agrarian products and on the whole agrarian sector of Ukraine are consider on the way of include in a world economic concord.
Keywords: World Trade Organization; competitiveness; agricultural sector of Ukraine; agrarian enterprises